Histopathological Comparison of Nasopharyngeal and Lung Tissue on Wistar Rats Induced with Formaldehyde - Abdiman, I Made Tobias; Wedayani, Anak Agung Ayu Niti; Prihatina, Lale Maulin; Restuningdyah, Novia Andansari Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Formaldehyde is a toxic substance commonly found in everyday life. Formaldehyde is also a carcinogenic exposure that often occurs in industrial areas. Formaldehyde itself is genotoxic and cytotoxic to tissues that can cause dysplasia to carcinoma. Inhalation of formaldehyde will expose the respiratory tract, which includes the nasopharynx and lung tissue to formaldehyde. Therefore, it is important to know the differences in tissue susceptibility to formaldehyde exposure related to the ability to cause dysplasia and carcinoma. Six Wistar rats were induced with formaldehyde through the inhalation method at a dose of 40 ppm for 16 weeks, and then terminated and subjected to histopathological examination. The degree of dysplasia will be assessed in both tissues, and then compared and tested statistically. The Mann-Whitney U statistical test showed a P value of 0.818, meaning that there was no significant difference between the degree of dysplasia in nasopharyngeal tissue and lung tissue. However, there was a difference in the rate of dysplasia progression between the two tissues, with nasopharyngeal tissue having a faster rate of progression. This difference in the rate of progression is related to the higher amount of formaldehyde deposition in the upper airway.